1997
DOI: 10.1097/00000539-199701000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Bispectral Index Correlates with Intraoperative Recall and Depth of Propofol-Induced Sedation

Abstract: The bispectral (BIS) index and 95% spectral edge frequency (SEF) of the electroencephalograph (EEG) have been used to study the anesthetic and sedative effects of intravenously (i.v.) administered drugs. This prospective study was designed to evaluate the effectiveness of the BIS index and 95% SEF for assessing the level of propofol-induced sedation and amnesia during regional anesthesia. Ten consenting adult patients undergoing surgery with regional anesthesia were administered propofol in increments of 10-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
139
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(148 citation statements)
references
References 8 publications
6
139
0
3
Order By: Relevance
“…Monitoring of the depth of anesthesia using the bispectral index (BIS) [29,30] allows us to objectively evaluate the level of sedation achieved and prevent the adverse events of overdose [31,32]. The BIS monitor has been found to be useful for dosing drugs and reducing recovery time in patients under sedation in diagnostic and therapeutic procedures [33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of the depth of anesthesia using the bispectral index (BIS) [29,30] allows us to objectively evaluate the level of sedation achieved and prevent the adverse events of overdose [31,32]. The BIS monitor has been found to be useful for dosing drugs and reducing recovery time in patients under sedation in diagnostic and therapeutic procedures [33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The bispectral index (BIS) is an excellent predictor of sedation and hypnosis produced by propofol, midazolam, isoflurane, and sevoflurane [1][2][3]. However, some studies have reported paradoxical BIS changes and inaccurate readings that do not always correlate with clinical measures of sedation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of EEG-based monitors of hypnosis such as the bispectral index or spectral entropy may help to optimize hypnotic administration [23, 24]. These monitors have been shown to reduce anesthetic doses, achieve greater hemodynamic stability, reduce the incidence of intraoperative awareness, and shorten recovery times [24, 25]. We used entropy monitoring to apply balanced anesthesia in the 2 groups.…”
Section: Discussionmentioning
confidence: 99%